English Department Students’ Beliefs Towards Plurilingualism And Its Influence on English Academic Achievement and Language Learning Styles In Mulawarman University - Feti Fahmimroah; Maria Teodora Ping; Iwan Setiawan (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
This study aimed at investigating the correlation between students’ beliefs towards plurilingualism with their English academic achievement and language learning styles both from quantitative and qualitative perspectives. A mixed method was used in this study and the researcher took students from the sixth semester of English department. To collect the data, the researcher distributed questionnaire and conducted interview. From the regression calculation, it was revealed that students’ beliefs towards plurilingualism correlated with their English academic achievement and language learning styles. Furthermore, from the interview, students’ views towards people who have the ability in many languages and their self-confidence from the aspects of belief towards plurilingualism held an important role for students’ English academic achievement. In addition, the students’ beliefs towards plurilingualism influenced their language learning styles, especially the frequency of the students English use in campus environment, whether inside or outside the classroom.